microRNA sequencing for biomarker detection in the diagnosis, classification and prognosis of Diffuse Large B Cell Lymphoma - Ane Larrabeiti-Etxebarria; Nerea Bilbao-Aldaiturriaga; Javier Arzuaga-Mendez; Maialen Martin-Arruti; Luca Cozzuto; Ayman Gaafar; Irune Ruiz-Diaz; Isabel Guerra; Idoia Martin-Guerrero; Elixabet Lopez-Lopez; Angela Gutierrez-Camino (Scientific Reports, 2023)
Abstract Despite being considered a single disease, Diffuse Large B Cell Lymphoma (DLBCL) presents with variable backgrounds, which results in heterogeneous outcomes among patients, with 40% of them still having primary refractory disease or relapse. Thus, novel biomarkers are needed. In addition, multiple factors regarding its pathogenesis remain unclear. In this context, recent investigations point to the relevance of microRNAs (miRNAs) in cancer. However, regarding DLBCL, there is inconsistency in the data reported. Therefore, in this work, the main goals were to determine a miRNA set with utility as biomarkers for DLBCL diagnosis, classification, prognosis and treatment response, as well as to decipher the mechanism of action of deregulated miRNAs in the origin of the disease. We analyzed miRNA expression in a cohort of 78 DLBCL patients and 17 controls using small RNA sequencing and performed a miRNA-mRNA interaction network analysis. This way, we were able to define new miRNA expression signatures for diagnosis, classification, treatment response and prognosis, and we identified plausible mechanisms of action by which deregulated miRNAs could be involved in DLBCL pathogenesis. In summary, our study remarks that miRNAs could play an important role in DLBCL.